2002
DOI: 10.1046/j.1440-1819.2002.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its correlates in a community population in a Japanese rural area

Abstract: Correlations of three aspects of quality of life (QOL) (health perception, life satisfaction, and self-confidence) with personality traits and early experiences were examined. Quality of life aspects were examined using 220 inhabitants in a rural community in Japan. Health perception was better among men than among women. Life satisfaction and self-confidence were better in people aged 55 or over than in those under 55. Among the current predictor variables, the Eysenck Personality Questionnaire neuroticism sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 97 publications
(146 reference statements)
0
5
0
Order By: Relevance
“…Eysenck proposed broad factors-extraversion, neuroticism, psychoticism, and lie-which he viewed as a sufficient model (or "paradigm") of personality [23][24][25]. Several Eysenck's personality questionnaires have been translated into Japanese [16,19,20] and have been applied in various research and clinical settings [26][27][28][29]. These studies have indicated that Eysenck's personality theory is as applicable to Japanese individuals as it is to Western individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Eysenck proposed broad factors-extraversion, neuroticism, psychoticism, and lie-which he viewed as a sufficient model (or "paradigm") of personality [23][24][25]. Several Eysenck's personality questionnaires have been translated into Japanese [16,19,20] and have been applied in various research and clinical settings [26][27][28][29]. These studies have indicated that Eysenck's personality theory is as applicable to Japanese individuals as it is to Western individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chang‐nian investigated QOL amongst Japanese involved in agriculture, and reported that age and gender were determining factors of QOL, and that satisfaction with life in males and elderly people was higher than that in females and younger subjects 26 . In addition, Kitamura et al ., investigating QOL among the general Japanese population, reported that satisfaction with life and self‐confidence was higher in people aged 55 years or older than in younger people 27 . Mori et al ., who used SF36 on Japanese subjects, also reported similar findings to our own; age was related to physical as well as mental aspects of QOL 20…”
Section: Discussionmentioning
confidence: 99%
“…Female gender seems to be related to lower quality of life, as reported in virtually all populations studied, including patients with diabetes (1), asthma (2), musculoskeletal pain (3), coronary disease (4), schizophrenia (5) as well as he general population (6,7). This trend has been found for young (8) as well as older people (9).…”
Section: Introductionmentioning
confidence: 69%
“…In previous research, a high level of neuroticism has been found to be more strongly associated with worse quality of life (7,11,15). However, these studies did not test models of complex relations and could not identify possible mediators, such as depressive state and perceived health.…”
Section: Discussionmentioning
confidence: 86%